Análise filogenética de Phytophthora capsici Leonian do estado de São Paulo baseada na seqüência de nucleotídeos da região ITS-5.8S rDNA - Rosa, Daniel Dias [UNESP]; De Marque, Janaina Marianno [UNESP]; Fenille, Roseli Chela; De Souza, Nilton Luiz [UNESP]; Kuramae, Eiko Eurya (Universidade Estadual de Maringa, 2003)
Phylogenetic analysis through morphological and cultural traits is considered inconsistent and hard to be scientifically accepted once there is no way to establish the direction of evolution on morphological traits. Molecular markers are suitable for phylogenetic analysis. The sequencing of ITS1 and ITS2 (internal transcribed spacers) regions and of 5.8S gene from ribosomal DNA were used to estimate the genetic variation and distance of 10 Phytophthora capsici isolates. The amount of genetic variation amongst isolated P. capsici from distinct regions of São Paulo State was 0.1 to 1.6 and 0.1 to 1.1% at ITS1 and ITS2, respectively, and a phylogenetic distance of about 78.5% between P. capsici and Phytophthora spp. was observed.
Phylogenetic analysis of Phytophthora capsici Leonian in the state of São Paulo based on the nucleotides sequence of ITS-5.8S rDNA region
Keywords: ITS; Phylogeny; Phytophthora sp.; Ribosomal DNA; internal transcribed spacer; ribosome DNA; Brazil; evolution; genetic variability; nonhuman; nucleotide sequence; phylogeny; Phytophthora; polymerase chain reaction; Leonia; Phytophthora capsici